Fatal left coronary artery dissection due to blunt chest trauma: A case report and literature review. (October 2019) - Violon, Florian; Lardenois, Emilie; Grafiadis, Patrick; Martrille, Laurent; Gauchotte, Guillaume
Blunt chest traumas can cause cardiac injuries and contusions. However, post-traumatic coronary artery dissections are quite uncommon. Here, we report the case of a 58-year-old woman who died suddenly 14 hours after a car accident. The macroscopic anomalies observed during the autopsy could not explain the death. However, microscopic examination revealed an acute left anterior descending coronary dissection, with a cleavage of the external layers of the media. The infiltration of polymorphonuclear neutrophils in the adventitia was a sign of the pre-mortem occurrence of this lesion and was compatible with the chronology of the accident. It was the only pathological finding that could explain the death, which was probably caused by a cardiac rhythm disorder triggered by acute ischaemia. We did not observe specific histological signs of cardiac necrosis, and we observed no significant atheroma, vasculitis or dysplasia in the left anterior descending coronary artery. We concluded that the dissection was secondary to the blunt chest trauma. Eleven case reports of lethal post-traumatic coronary dissection have been reported in the literature. Most of them involved male subjects aged <60 years old following a traffic accident, and were localised to the left coronary artery or one of its branches. Histological specific signs of myocardial ischaemia were present in only 33% of the cases. In this case, only microscopic examination could identify the dissection. This pathology may be underdiagnosed, and it highlights the necessity to undertake rigorous examination of the heart and coronary arteries following blunt chest trauma.